Research, innovation and career development: Experience and prospective of Forest Research Institute of Malaysia (FRIM) / Abd Latif Mohmod, Hoi Why Kong and Ashaari Mohd. Amin - Mohmod, Abd Latif; Hoi, Why Kong; Mohd. Amin, Ashaari (2005)
Educationists and researchers are challenged to contribute to nation building. The avenues of successes are measured by contributions we make from the inputs and outputs of research, innovation and career development. FRlM's output is in the commercialization of R&D products which adopted "Research with Impact" philosophy. Commercialization effort is not a stand-alone endeavor. There are many indicators to show successful commercialization effort. Staff development enhanced is to be closely aligned with the business objectives. Reciprocally, management needs to develop policies and procedures to advance professional growth and opportunities for all staff levels. Research helps in building institutional and national capacities and Intellectual Property Rights. All these lead to a more meaningful partnerships leading to multihued added values. Other requirements to provide impacts come in assorted forms and character. The elements begin with senses and actions of look, feel, evaluate, decide and execute. FRlM's Strategies for R&D commercialization are also enlightened.